A coating composition and its preparation method and application
By using raw materials such as PMOS precursors to form a coating with periodic arrangement of skeletons, the problem of insufficient hardness and poor wear resistance of cement-based inorganic artificial stone anti-fouling coating is solved, and high hardness, high wear resistance, excellent antifouling and corrosion resistance are achieved.
Patent Information
- Application Number
- CN202311009142.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2043-08-10
AI Technical Summary
The anti-fouling coating of existing cement-based inorganic artificial stones has problems such as insufficient hardness, poor wear resistance, poor anti-fouling and corrosion resistance during use, which is difficult to meet the long-term use and aesthetic requirements.
The PMOS precursor, structural guide agent, ceramic precursor, alkoxysilane and fluorosilane are used to form a coating with periodic arrangement of the skeletons through self-polymerization and radical polymerization, which enhances mechanical strength and stability, and reduces surface energy through fluorine-containing groups to improve soil resistance and corrosion resistance.
A transparent, wear-resistant and anti-fouling coating has been formed. The pencil has a hardness of 9H, and its wear-resistant and anti-fouling properties have been significantly improved. It can be used on the surface of cement-based inorganic artificial stone for a long time and maintain a good appearance state.
Smart Images

Figure CN117143518B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coatings, and in particular relates to a coating composition and a preparation method and application thereof. Background Art
[0002] Cement-based inorganic artificial stone is increasingly used in the field of building materials. The surface of this type of artificial stone decorative material has a certain porosity and surface roughness. In daily use, it is inevitably contaminated and corroded by various polluting liquids, including common liquids such as soy sauce, milk, cola, strong tea and red wine, as well as various acidic liquids that are corrosive to alkaline panels, such as vinegar and citric acid. These pollutants are easily physically adsorbed with the pores in the material, and they also react with active points such as free hydroxyl groups on the surface of the substrate to form chemical adsorption or corrosion. These stains are easy to accumulate and difficult to remove, affecting the appearance and service life. At the same time, the use scenarios such as cement-based inorganic artificial stone floors require the protective coating to have high transparency, and the surface should not produce defects such as scratches as much as possible during long-term use, so as to maintain a good appearance and a long service life.
[0003] At present, the antifouling of cement-based inorganic artificial stone mainly adopts penetrating and coating protective agents. Some researchers have proposed a cleaning method for inorganic artificial stone, which uses fine polishing and cleaning agent treatment to improve the antifouling performance of inorganic artificial stone. Some researchers have developed a penetrating film-forming stone protective agent of modified nano-titanium dioxide hydrosol, which has a high contact angle and excellent anti-oil effect. These penetrating protective agents effectively improve the pollution problem of cement-based inorganic artificial stone, but the traditional penetrating protective agents have limited improvement on the antifouling performance of cement-based inorganic artificial stone, the effect lasts for a short time, and the antifouling and anti-corrosion performance are not outstanding. For example, the treatment of anti-seepage sealers such as crystal paste and glaze sealant requires regular maintenance, and the labor time cost is high. Some crystal pastes and glaze sealants will even react with acidic substances and be corroded, causing the protective layer to be destroyed.
[0004] In addition, although the surface film-forming coating type protective agent has good antifouling and anticorrosion effects, this type of protective coating has high antifouling and anticorrosion properties, and can meet the antifouling and anticorrosion requirements of cement-based inorganic artificial stone. However, the hardness of this type of coating is not enough, and the pencil hardness is lower than 6H. During the use of cement-based inorganic artificial stone floors, a large number of scratches are easily generated, which affects the appearance and service life of the substrate. Therefore, it is still necessary to develop a new coating composition, which can form a transparent, wear-resistant, and antifouling coating when applied to the surface of cement-based inorganic artificial stone. Summary of the invention
[0005] The present invention aims to solve at least one of the above technical problems existing in the prior art. To this end, the present invention provides a coating composition, which can form a transparent, wear-resistant and anti-fouling coating when applied to the surface of cement-based inorganic artificial stone.
[0006] The present invention also provides a method for preparing the coating composition.
[0007] The invention also provides an antifouling coating.
[0008] The invention also provides a method for preparing the antifouling coating.
[0009] The invention also provides application of the antifouling coating on the surface of cement-based inorganic artificial stone.
[0010] The first aspect of the present invention provides a coating composition, wherein the raw materials for preparing the coating composition include a PMOS precursor, a structure directing agent, a ceramic precursor, an alkoxysilane and a fluorosilane, wherein the functionality of the alkoxysilane is ≥2, and the PMOS precursor has a structure as shown in formula (I) or formula (II):
[0011]
[0012] Among them, R 1 and R 2 At least one independently selected from alkanes, alkenes, and amines, R 3 Selected from methyl or ethyl.
[0013] One of the technical solutions of the present invention regarding the coating composition has at least the following beneficial effects:
[0014] The coating composition of the present invention uses a PMOS precursor with a special structure, which can be self-polymerized by a structure-directing agent to form a skeleton structure with a periodic arrangement. Free active points still exist in the periodic skeleton, which may react with stains and chemicals. A free radical polymerization reaction further occurs between the alkoxysilane with a functionality ≥ 2 and the network skeleton formed by the ceramic precursor and the free active points, so that inorganic ceramic chemical bonds are interspersed in the periodic skeleton formed by the PMOS precursor, thereby enhancing the mechanical strength and stability of the coating structure, so that the formed coating has the characteristics of high hardness and high wear resistance, and at the same time has high scratch resistance.
[0015] The coating composition of the present invention has a large number of silicon-oxygen bonds, fluorine-containing groups and other groups connected to the active points of the periodic skeleton, and various functional groups are orderly arranged in the skeleton by utilizing the periodic arrangement of the skeleton, thereby reducing free active points. At the same time, the orderly arranged fluorine-containing groups in the fluorosilane can reduce the surface energy of the coating, thereby reducing the adsorption of pollutants and the corrosion of chemicals, so that the coating formed by the coating composition has excellent antifouling and anticorrosion properties.
[0016] The coating composition of the present invention has active points in the skeleton that physically and chemically react with the groups and ions of the coupling agent on the surface of the organic or inorganic substrate, thereby achieving a firm bond with the substrate surface and having a high bonding force.
[0017] The antifouling coating formed by the coating composition of the present invention after drying is a transparent, wear-resistant antifouling coating. The pencil hardness of the coating can reach 9H, the number of frictions with 1kg of steel wool is greater than 4000 times, and the color difference value of the coating is ΔE≤1.5 after being stained with stains for no less than 24 hours. The tolerable stains include: corrosive stains (including but not limited to vinegar, cola), dye stains (including but not limited to strong tea, ink), and grease stains (including but not limited to animal oil and vegetable oil). The visible light transmittance is ≥95%, and after 1000h of xenon lamp aging acceleration time, the coating does not break or turn yellow, and the color difference ΔE≤1. The chemical corrosion resistance is better than C4 level. After the coating is applied to the surface of artificial stone, the waterproofness of the artificial stone is ≥95%. The bonding strength cross-hatch method level is better than level 1.
[0018] The antifouling coating formed by the coating composition of the present invention after drying has better antifouling and anticorrosion effects than the artificial stone permeable protective agent, and the effect lasts longer. Compared with the general protective coating, it has better transparency, higher hardness, and better wear resistance, and can be used on the ground for a long time.
[0019] In the coating composition of the present invention, the PMOS precursor can be either homemade or commercially available. Its structure conforms to the structure of the PMOS precursor defined in the present invention. Based on the structure of the PMOS precursor defined in the present invention, under the induction of a structure directing agent, a silicon-oxygen skeleton with a periodic arrangement sequence is formed by self-polymerization reaction, and the mechanical strength and stability are superior to other silicon-oxygen structures.
[0020] The coating composition of the invention has a solvent system that meets environmental protection requirements, and the coating is non-toxic and tasteless after being completely cured.
[0021] According to some embodiments of the present invention, the molecular weight of the PMOS precursor is ≤10,000.
[0022] According to some embodiments of the present invention, the preparation raw materials include, by weight:
[0023] PMOS precursor: 100 parts,
[0024] Structure directing agent: 0.1 to 0.5 parts,
[0025] Ceramic precursor: 50 to 90 parts,
[0026] Alkoxysilane: 50 to 200 parts,
[0027] Fluorosilane: 10 to 20 parts.
[0028] According to some embodiments of the invention, the structure directing agent comprises at least one of a triblock copolymer, hexadecyltrimethylammonium bromide, hexadecylpyridinium bromide, and alkyltrimethylammonium chloride.
[0029] The dosage of the structure directing agent and the solution dropping speed should be within a certain range to prevent excessive side reactions from causing large defects in the periodically arranged skeleton.
[0030] According to some embodiments of the invention, the structure directing agent comprises P123.
[0031] According to some embodiments of the present invention, the ceramic precursor includes at least one of zirconium n-propoxide, tetraethyl orthosilicate and butyl orthotitanate.
[0032] Multiple connected silicon-oxygen bonds are interspersed in the periodically arranged skeleton, making the coating skeleton structure more stable and having better performance. Fluorine-containing branches are added to the branches of the skeleton to form fluorine-containing groups with a periodic structure, making the coating more hydrophobic.
[0033] According to some embodiments of the present invention, the alkoxysilane includes at least two of methyltriethoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, phenyltriethoxysilane, phenyltrimethoxysilane and dimethyldiethoxysilane.
[0034] According to some embodiments of the present invention, the fluorosilane includes at least one of dodecafluoroheptylpropyltrimethoxysilane, perfluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane, and heptadecafluorodecyltrimethoxysilane.
[0035] According to some embodiments of the present invention, in parts by weight, when the PMOS precursor is 100 parts, the preparation raw material further comprises:
[0036] Organic solvent: 300 to 500 parts
[0037] Catalyst: 10 to 15 parts,
[0038] Water: 30 to 50 parts.
[0039] According to some embodiments of the present invention, the organic solvent comprises at least one selected from methanol, ethanol, n-propanol and n-butanol.
[0040] According to some embodiments of the present invention, the amount of the organic solvent used is about 1 to 3 times the total amount of the remaining reagents.
[0041] According to some embodiments of the present invention, the catalyst comprises at least one of an inorganic base, an alkali metal hydroxide or a metal carboxylate.
[0042] The second aspect of the present invention provides a method for preparing the coating composition, comprising the following steps:
[0043] Using the structure directing agent, the PMOS precursor and part of the organic solvent, the catalyst and water, a polysiloxane solution is prepared;
[0044] Using the ceramic precursor, alkoxysilane, fluorosilane and part of the organic solvent, catalyst and water, a fluorine-modified silica sol is prepared;
[0045] After the polysiloxane solution and part of the organic solvent are mixed evenly, the fluorine-modified silica sol is added, and the coating composition is obtained after refluxing.
[0046] A technical solution in the method for preparing a coating composition of the present invention has at least the following beneficial effects:
[0047] The preparation method of the coating composition of the present invention does not require expensive equipment and complicated process control, has undemanding reaction conditions, has readily available raw materials, has low production costs, and is easy to industrialize.
[0048] According to some embodiments of the present invention, in the method for preparing the coating composition, in addition to the PMOS precursor, structure directing agent, ceramic precursor, alkoxysilane, fluorosilane, organic solvent, catalyst and water, other additives such as thixotropic agent and wetting agent may be added according to specific needs, such as the specific conditions of the construction process and substrate type.
[0049] One of the functions of thixotropic agents is to ensure that the coating can adapt to different construction processes and prevent the solid fillers that may be added from settling.
[0050] One of the functions of a wetting agent is to ensure that the coating can have a good wetting effect on substrates with uneven surface energy and quickly level them.
[0051] According to some embodiments of the present invention, the thixotropic agent includes a polyurea type thixotropic agent and a modified polyurea type thixotropic agent.
[0052] According to some embodiments of the present invention, the wetting agent comprises a silicone-based wetting agent.
[0053] According to some embodiments of the present invention, during the method for preparing the coating composition, "part of the organic solvent" can be added as appropriate, and the general amount added is 1 to 3 times the total amount of the other reagents in this step.
[0054] According to some embodiments of the present invention, the method for preparing the polysiloxane solution is:
[0055] A1: Mix the structure directing agent and part of the organic solvent, mix part of the catalyst and water, add the mixed solution of the catalyst and water to the mixed solution of the structure directing agent and the solvent under stirring, adjust the pH, and reflux at 100° C. to 120° C. for 1 h to 1.5 h;
[0056] A2: Cooling the solution prepared in step A1 to 60° C. to 80° C., mixing part of the organic solvent and the PMOS precursor, and adding the mixture to the cooled solution prepared in step A1, and reflux for 2 h to 3 h;
[0057] A3: Stop heating, cool to room temperature under stirring, and perform silica gel column chromatography to obtain the polysiloxane solution.
[0058] According to some embodiments of the present invention, the method for preparing the polysiloxane solution may be:
[0059] Mix part of the organic solvent and the structure directing agent evenly and introduce them into a three-necked flask, keep stirring at a speed of 1500rpm to 2000rpm;
[0060] After the catalyst and deionized water are evenly mixed, slowly drip the mixed solution of the catalyst and deionized water into the three-necked flask under stirring, with a dripping speed of 2mL / min to 3mL / min, adjust the pH of the solution to 9 to 10, and continue to reflux at 100℃ to 120℃ for 1h to 1.5h;
[0061] The solution temperature is lowered to 60°C to 80°C, and part of the organic solvent and the PMOS precursor are mixed and added into a three-necked flask at a dropping speed of 2mL / min to 3mL / min, and then refluxed for 2h to 3h;
[0062] The heating was stopped, and magnetic stirring was maintained. After the three-necked flask was cooled to room temperature by air, silica gel column chromatography was performed to obtain a polysiloxane solution having a periodic skeleton structure.
[0063] According to some embodiments of the present invention, for silica gel column chromatography separation, the mobile phase may be a petroleum ether / ethyl acetate system with a volume ratio of about 50 to 90: 1. The silica gel may be 100 to 200 mesh silica gel.
[0064] According to some embodiments of the present invention, the preparation method of the fluorine-modified silica sol is:
[0065] B1: mixing the ceramic precursor, alkoxysilane and part of the organic solvent;
[0066] B2: Mix part of the catalyst and water, add the mixed solution of the catalyst and water to the mixed solution prepared in step B1 under stirring, adjust the pH, and reflux at 60° C. to 80° C. for 1 h to 1.5 h;
[0067] B3: adding the fluorosilane to the mixed solution prepared in step B2, and continuing to reflux for 1 h to 1.5 h to obtain the fluorine-modified silica sol.
[0068] According to some embodiments of the present invention, the preparation method of the fluorine-modified silica sol may be:
[0069] Mix part of the organic solvent, ceramic precursor and alkoxysilane evenly, put them into a three-necked flask, and stir them magnetically at a speed of 1500 rpm to 2000 rpm;
[0070] After the mixture is completely stirred, slowly drip the catalyst and deionized water mixed solution into the three-necked flask under stirring at a rate of 2 mL / min to 3 mL / min. Adjust the pH of the solution to 9 to 10 and reflux at 60 to 80 °C for 1 h to 1.5 h.
[0071] Then, the fluorosilane mixture is added dropwise into the three-necked flask at a dropping speed of 2 mL / s to 4 mL / s, and the temperature is maintained to continue to reflux for 1.5 h to 2 h to obtain fluorine-modified silica sol.
[0072] According to some embodiments of the present invention, in the method for preparing the coating composition, the polysiloxane solution and part of the organic solvent are mixed, and then the fluorine-modified silica sol is added, and the coating composition is obtained after refluxing. The specific method may be:
[0073] Mix part of the organic solvent and the polysiloxane solution evenly, and put them into a three-necked flask, and keep magnetic stirring at a speed of 1500rpm to 2000rpm;
[0074] Then, fluorine-modified silica sol was added dropwise into a three-necked flask at a dropping speed of 2 mL / s to 4 mL / s, and refluxed at 60°C to 80°C for 1.5 h to 2 h;
[0075] Finally, the prepared solution was filtered through a 200-mesh copper mesh to obtain a coating composition.
[0076] The third aspect of the present invention provides an antifouling coating obtained by curing the coating composition.
[0077] One of the technical solutions of the present invention regarding the antifouling coating has at least the following beneficial effects:
[0078] The antifouling coating of the present invention is obtained by curing the coating composition of the present invention, and thus, at least has all the beneficial effects of the coating composition. Specifically:
[0079] The antifouling coating of the present invention uses a PMOS precursor with a special structure, which can be self-polymerized by a structure-directing agent to form a skeleton structure with a periodic arrangement. Free active points still exist in the periodic skeleton, which may react with stains and chemicals. A free radical polymerization reaction further occurs between the network skeleton formed by the alkoxysilane with a functionality ≥ 2 and the ceramic precursor and the free active points, so that inorganic ceramic chemical bonds are interspersed in the periodic skeleton formed by the PMOS precursor, thereby enhancing the mechanical strength and stability of the coating structure, so that the formed coating has the characteristics of high hardness and high wear resistance, and at the same time has high scratch resistance.
[0080] The antifouling coating of the present invention has a large number of silicon-oxygen bonds, fluorine-containing groups and other groups connected to the active points of the periodic skeleton. By utilizing the periodic arrangement of the skeleton, various functional groups are orderly arranged in the skeleton, thereby reducing free active points. At the same time, the orderly arranged fluorine-containing groups in the fluorosilane can reduce the surface energy of the coating, thereby reducing the adsorption of pollutants and the corrosion of chemicals, so that the coating formed by the coating composition has excellent antifouling and anticorrosion properties.
[0081] The antifouling coating of the present invention has active points in the skeleton that physically and chemically react with the groups and ions of the coupling agent on the surface of the organic or inorganic substrate, thereby achieving a firm bond with the substrate surface and having a high bonding force.
[0082] The antifouling coating of the present invention is a transparent, wear-resistant antifouling coating. The pencil hardness of the coating can reach 9H, the number of frictions with 1kg of steel wool is greater than 4000 times, and the color difference value of the coating is ΔE≤1.5 after being stained for no less than 24 hours. The tolerable stains include: corrosive stains (including but not limited to vinegar, cola), dye stains (including but not limited to strong tea, ink), and grease stains (including but not limited to animal oil and vegetable oil). The visible light transmittance is ≥95%, and after 1000h of xenon lamp aging acceleration time, the coating does not break or turn yellow, and the color difference ΔE≤1. The chemical corrosion resistance is better than C4 level. After the coating is applied to the surface of artificial stone, the waterproofness of artificial stone is ≥95%. The bonding strength cross-cutting method level is better than level 1.
[0083] The antifouling coating of the present invention has better antifouling and anticorrosion effects than artificial stone permeable protective agents, and the effects last longer. Compared with general protective coatings, the antifouling coating has better transparency, higher hardness, and better wear resistance, and can be used on the ground for a long time.
[0084] In the antifouling coating of the present invention, the PMOS precursor can be either homemade or commercially available. Its structure conforms to the structure of the PMOS precursor defined in the present invention. Based on the structure of the PMOS precursor defined in the present invention, under the induction of a structure directing agent, a silicon-oxygen skeleton with a periodic arrangement sequence is formed by self-polymerization reaction, and the mechanical strength and stability are superior to other silicon-oxygen structures.
[0085] In the antifouling coating of the present invention, the solvent system meets environmental protection requirements, and the coating is non-toxic and tasteless after being completely cured.
[0086] According to some embodiments of the present invention, the antifouling coating has a thickness of 5 μm to 15 μm.
[0087] The fourth aspect of the present invention provides a method for preparing the antifouling coating, the method comprising:
[0088] A curing agent is added to the coating composition, mixed evenly, and then the coating is applied to the surface of the substrate, and dried to obtain the antifouling coating.
[0089] A technical solution in the method for preparing an antifouling coating of the present invention has at least the following beneficial effects:
[0090] The antifouling coating of the present invention is easy to construct, has undemanding curing conditions, and is suitable for large-area coating.
[0091] According to some embodiments of the present invention, the method for preparing the antifouling coating may be:
[0092] After scrubbing the surface of the artificial stone substrate with alcohol and acetone respectively, leave it for at least half an hour to allow the artificial stone substrate to fully dry;
[0093] After the coupling agent and ethanol are mixed evenly, wipe them evenly on the surface of the substrate and leave them for 0.5h to 1.5h;
[0094] Add curing agent to the coating composition, stir magnetically to mix thoroughly, and then proceed with subsequent coating preparation operations. The mass ratio of the coating composition to the curing agent is between 6 and 8:1;
[0095] Spray a transparent wear-resistant and antifouling coating on the surface of the substrate, leave it alone for natural curing, and then bake it in an oven at 60°C to 80°C for 6h to 12h to form a transparent wear-resistant and antifouling coating.
[0096] According to some embodiments of the present invention, the spraying is performed by air spraying with a pressure of 0.2 MPa to 0.3 MPa.
[0097] According to some embodiments of the present invention, the spraying distance is 20 mm to 30 mm.
[0098] According to some embodiments of the present invention, the humidity is between 40% and 60%, and the temperature is between 15°C and 30°C.
[0099] According to some embodiments of the present invention, the coupling agent is at least one of KH550, KH560, A171, A151 and KHA172.
[0100] According to some embodiments of the present invention, the curing agent includes at least one of 3-aminopropyltriethoxysilane and 3-glycidyloxypropyltrimethoxysilane.
[0101] According to some embodiments of the present invention, the curing agent includes at least one of KH550 and KH560.
[0102] According to some embodiments of the present invention, the mass ratio of the curing agent to the coating composition is 1:6-8.
[0103] According to some embodiments of the present invention, the substrate includes cement-based inorganic artificial stone.
[0104] The fifth aspect of the present invention provides the use of the antifouling coating on the surface of cement-based inorganic artificial stone.
[0105] The present invention provides a technical solution for the application of antifouling coating on the surface of cement-based inorganic artificial stone, which has at least the following beneficial effects:
[0106] The antifouling coating of the present invention is a transparent, wear-resistant antifouling coating. When used on the surface of cement-based inorganic artificial stone, the pencil hardness of the coating can reach 9H, the number of frictions with 1kg of steel wool is greater than 4000 times, and the color difference value of the coating is ΔE≤1.5 after being stained with stains for no less than 24 hours. The tolerable stains include: corrosive stains (including but not limited to vinegar, cola), dye stains (including but not limited to strong tea, ink), and grease stains (including but not limited to animal oil and vegetable oil). The visible light transmittance is ≥95%, and after 1000h of xenon lamp aging acceleration time, the coating does not break or turn yellow, and the color difference ΔE≤1. The chemical corrosion resistance is better than C4 level. After the coating is applied to the surface of artificial stone, the waterproofness of artificial stone is ≥95%. The bonding strength cross-cutting method level is better than level 1.
[0107] The antifouling coating of the present invention has better antifouling and anticorrosion effects than artificial stone permeable protective agents, and the effects last longer. Compared with general protective coatings, the antifouling coating has better transparency, higher hardness, and better wear resistance, and can be used on the ground for a long time.
[0108] In the antifouling coating of the present invention, the PMOS precursor can be either homemade or commercially available. Its structure conforms to the structure of the PMOS precursor defined in the present invention. Based on the structure of the PMOS precursor defined in the present invention, under the induction of a structure directing agent, a silicon-oxygen skeleton with a periodic arrangement sequence is formed by self-polymerization reaction, and the mechanical strength and stability are superior to other silicon-oxygen structures.
[0109] In the antifouling coating of the present invention, the solvent system meets environmental protection requirements, and the coating is non-toxic and tasteless after being completely cured. BRIEF DESCRIPTION OF THE DRAWINGS
[0110] Figure 1 This is an appearance diagram of the coating composition prepared in Example 1.
[0111] Figure 2 The following are the wear resistance test results of the coatings of the embodiments and comparative examples.
[0112] Figure 3 The following are the stain resistance test results of the coatings of the embodiments and comparative examples. DETAILED DESCRIPTION
[0113] The following are specific embodiments of the present invention, and the technical solutions of the present invention are further described in conjunction with the embodiments, but the present invention is not limited to these embodiments.
[0114] In some embodiments of the present invention, the present invention provides a coating composition, the raw materials for preparing the coating composition include a PMOS precursor, a structure directing agent, a ceramic precursor, an alkoxysilane and a fluorosilane, the functionality of the alkoxysilane is ≥2, and the PMOS precursor has a structure as shown in formula (I) or formula (II):
[0115]
[0116] Among them, R 1 and R 2 At least one or more independently selected from alkanes, alkenes, and amines, R 3 Selected from methyl or ethyl.
[0117] It can be understood that the coating composition of the present invention, using a PMOS precursor with a special structure, can self-polymerize through a structure-directing agent to form a skeleton structure with a periodic arrangement. Free active points still exist in the periodic skeleton, which may react with stains and chemicals. Through alkoxysilanes with a functionality ≥ 2 and a network skeleton formed by a ceramic precursor, free radical polymerization reactions further occur between the free active points, thereby interspersing inorganic ceramic chemical bonds in the periodic skeleton formed by the PMOS precursor, enhancing the mechanical strength and stability of the coating structure, so that the formed coating has the characteristics of high hardness and high wear resistance, and at the same time has high scratch resistance.
[0118] It can also be understood that the coating composition of the present invention has a large number of silicon-oxygen bonds, fluorine-containing groups and other groups connected to the active points of the periodic skeleton, and the various functional groups are arranged in an orderly manner in the skeleton by utilizing the periodic arrangement of the skeleton, thereby reducing the free active points. At the same time, the orderly arranged fluorine-containing groups in the fluorosilane can reduce the surface energy of the coating, thereby reducing the adsorption of pollutants and the corrosion of chemicals, so that the coating formed by the coating composition has excellent antifouling and anticorrosion properties.
[0119] In addition, the active points in the skeleton of the coating composition of the present invention react physically and chemically with the groups and ions of the coupling agent on the surface of the organic or inorganic substrate, thereby achieving a firm bond with the substrate surface and having a high bonding force.
[0120] It can be understood that the antifouling coating formed by the coating composition of the present invention after drying is a transparent, wear-resistant antifouling coating. The pencil hardness of the coating can reach 9H, the number of frictions with 1kg of steel wool is greater than 4000 times, and the color difference value of the coating is ΔE≤1.5 after being stained with stains for no less than 24 hours. The tolerable stains include: corrosive stains (including but not limited to vinegar, cola), dye stains (including but not limited to strong tea, ink), and grease stains (including but not limited to animal oil and vegetable oil). The visible light transmittance is ≥95%, and after 1000h of xenon lamp aging acceleration time, the coating does not break or turn yellow, and the color difference ΔE≤1. The chemical corrosion resistance is better than C4 level. After the coating is applied to the surface of artificial stone, the waterproofness of artificial stone is ≥95%. The bonding strength cross-cutting method level is better than level 1.
[0121] It can be understood that the antifouling coating formed by the coating composition of the present invention after drying has better antifouling and anticorrosion effects than the artificial stone permeable protective agent, and the effect lasts longer. Compared with the general protective coating, it has better transparency, higher hardness, and more wear resistance, and can be used on the ground for a long time.
[0122] It is understood that in the coating composition of the present invention, the PMOS precursor can be either homemade or commercially available. Its structure conforms to the structure of the PMOS precursor defined in the present invention. Based on the structure of the PMOS precursor defined in the present invention, under the induction of the structure directing agent, the self-polymerization reaction forms a silicon-oxygen skeleton with a periodic arrangement order, and the mechanical strength and stability are better than other silicon-oxygen structures.
[0123] It can be understood that the coating composition of the present invention and the solvent system meet environmental protection requirements, and the coating is non-toxic and odorless after being fully cured.
[0124] In some embodiments of the present invention, the molecular weight of the PMOS precursor is ≤10,000.
[0125] In some embodiments of the present invention, the raw materials for preparation include, by weight:
[0126] PMOS precursor: 100 parts,
[0127] Structure directing agent: 0.1 to 0.5 parts,
[0128] Ceramic precursor: 50 to 90 parts,
[0129] Alkoxysilane: 50 to 200 parts,
[0130] Fluorosilane: 10 to 20 parts.
[0131] In some embodiments of the present invention, the structure directing agent includes at least one of a triblock copolymer, cetyltrimethylammonium bromide, cetylpyridinium bromide, and alkyltrimethylammonium chloride.
[0132] The dosage of the structure directing agent and the solution dropping speed should be within a certain range to prevent excessive side reactions from causing large defects in the periodically arranged skeleton.
[0133] In some embodiments of the present invention, the structure directing agent is P123. P123 is a copolymer composed of three different blocks. It is composed of three blocks of polyoxyethylene (EO), polypropylene (PO) and polyethylene (EO), so it is also called EO-PO-EO copolymer. This copolymer has two different blocks of hydrophobicity and hydrophilicity, and can form microstructures in solution, such as micelles, transparent liquid crystal phases, etc., and is widely used in the field of materials science, especially in the preparation of nanomaterials, catalysts, drug delivery systems and surface coatings. It has important application value.
[0134] In some embodiments of the present invention, the ceramic precursor includes at least one of zirconium n-propoxide, tetraethyl orthosilicate, and butyl orthotitanate.
[0135] Multiple connected silicon-oxygen bonds are interspersed in the periodically arranged skeleton, making the coating skeleton structure more stable and having better performance. Fluorine-containing branches are added to the branches of the skeleton to form fluorine-containing groups with a periodic structure, making the coating more hydrophobic.
[0136] In some embodiments of the present invention, the alkoxysilane includes at least two of methyltriethoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, phenyltriethoxysilane, phenyltrimethoxysilane and dimethyldiethoxysilane.
[0137] In some embodiments of the present invention, the fluorosilane includes at least one of dodecafluoroheptylpropyltrimethoxysilane, perfluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane, and heptadecafluorodecyltrimethoxysilane.
[0138] In some embodiments of the present invention, when the PMOS precursor is 100 parts by weight, the prepared raw materials further include:
[0139] Organic solvent: 300 to 500 parts,
[0140] Catalyst: 10 to 15 parts,
[0141] Water: 30 to 50 parts.
[0142] In some embodiments of the present invention, the organic solvent includes at least one selected from methanol, ethanol, n-propanol and n-butanol.
[0143] In some embodiments of the present invention, the amount of the organic solvent used is about 1 to 3 times the total amount of the remaining reagents.
[0144] In some embodiments of the present invention, the catalyst includes at least one of an inorganic base, an alkali metal hydroxide, or a metal carboxylate.
[0145] In some other embodiments of the present invention, the present invention provides a method for preparing a coating composition, comprising the following steps:
[0146] A polysiloxane solution is prepared by using a structure directing agent, a PMOS precursor, a portion of an organic solvent, a catalyst and water;
[0147] Fluorine-modified silica sol is prepared by using ceramic precursor, alkoxysilane, fluorosilane, part of organic solvent, catalyst and water;
[0148] After the polysiloxane solution and part of the organic solvent are mixed evenly, the fluorine-modified silica sol is added, and the coating composition of the present invention is obtained after refluxing.
[0149] It can be understood that the preparation method of the coating composition of the present invention does not require expensive equipment and complex process control, the reaction conditions are not harsh, the raw materials are easily available, the production cost is low, and it is easy to industrialize production.
[0150] It should be noted that in the preparation method of the coating composition, in addition to the PMOS precursor, structure directing agent, ceramic precursor, alkoxysilane, fluorosilane, organic solvent, catalyst and water, other additives such as thixotropic agent and wetting agent can be added according to specific needs, such as the specific conditions of the construction process and substrate type.
[0151] It is understood that one of the functions of the thixotropic agent is to ensure that the coating can adapt to different construction processes and prevent the solid fillers that may be added from settling.
[0152] It can also be understood that one of the functions of the wetting agent is to ensure that the coating can have a good wetting effect on the substrate with uneven surface energy and quickly level it.
[0153] In some embodiments of the present invention, the thixotropic agent includes a polyurea thixotropic agent and a modified polyurea thixotropic agent.
[0154] In some embodiments of the present invention, the wetting agent includes a silicone-based wetting agent.
[0155] In some embodiments of the present invention, the preparation method of the polysiloxane solution is:
[0156] A1: Mix the structure directing agent and part of the organic solvent, mix part of the catalyst and water, add the mixed solution of the catalyst and water to the mixed solution of the structure directing agent and the solvent under stirring, adjust the pH, and reflux at 100℃~120℃ for 1h~1.5h;
[0157] A2: Cool the solution prepared in step A1 to 60°C to 80°C, mix part of the organic solvent and the PMOS precursor, add the mixture to the cooled solution prepared in step A1, and reflux for 2h to 3h;
[0158] A3: Stop heating, cool to room temperature under stirring, and perform silica gel column chromatography to obtain a polysiloxane solution.
[0159] In some embodiments of the present invention, the preparation method of the polysiloxane solution may be:
[0160] Mix part of the organic solvent and the structure directing agent evenly and introduce them into a three-necked flask, keep stirring at a speed of 1500rpm to 2000rpm;
[0161] After the catalyst and deionized water are evenly mixed, slowly drip the mixed solution of the catalyst and deionized water into the three-necked flask under stirring, with a dripping speed of 2mL / min to 3mL / min, adjust the pH of the solution to 9 to 10, and continue to reflux at 100℃ to 120℃ for 1h to 1.5h;
[0162] The solution temperature is lowered to 60°C to 80°C, and part of the organic solvent and the PMOS precursor are mixed and added into a three-necked flask at a dropping speed of 2mL / min to 3mL / min, and then refluxed for 2h to 3h;
[0163] The heating was stopped, and magnetic stirring was maintained. After the three-necked flask was cooled to room temperature by air, silica gel column chromatography was performed to obtain a polysiloxane solution having a periodic skeleton structure.
[0164] In some embodiments of the present invention, for silica gel column chromatography separation, the mobile phase may be a petroleum ether / ethyl acetate system with a volume ratio of about 50 to 90: 1. The silica gel may be 100 to 200 mesh silica gel.
[0165] In some embodiments of the present invention, the preparation method of fluorine-modified silica sol is:
[0166] B1: Mix the ceramic precursor, alkoxysilane and part of the organic solvent;
[0167] B2: Mix part of the catalyst and water, add the mixed solution of the catalyst and water to the mixed solution prepared in step B1 under stirring, adjust the pH, and reflux at 60° C. to 80° C. for 1 h to 1.5 h;
[0168] B3: Add fluorosilane to the mixed solution prepared in step B2, and continue to reflux for 1 h to 1.5 h to obtain fluorine-modified silica sol.
[0169] In some embodiments of the present invention, the preparation method of fluorine-modified silica sol may be:
[0170] Mix part of the organic solvent, ceramic precursor and alkoxysilane evenly, put them into a three-necked flask, and stir them magnetically at a speed of 1500 rpm to 2000 rpm;
[0171] After the mixture is completely stirred, slowly drip the catalyst and deionized water mixed solution into the three-necked flask under stirring at a rate of 2 mL / min to 3 mL / min. Adjust the pH of the solution to 9 to 10 and reflux at 60 to 80 °C for 1 h to 1.5 h.
[0172] Then, the fluorosilane mixture is added dropwise into the three-necked flask at a dropping speed of 2 mL / s to 4 mL / s, and the temperature is maintained to continue to reflux for 1.5 h to 2 h to obtain fluorine-modified silica sol.
[0173] In some embodiments of the present invention, in the method for preparing the coating composition, after the polysiloxane solution and part of the organic solvent are mixed, the fluorine-modified silica sol is added, and the coating composition of the present invention is obtained after refluxing. The specific method can be:
[0174] Mix part of the organic solvent and the polysiloxane solution evenly, and put them into a three-necked flask, and keep magnetic stirring at a speed of 1500rpm to 2000rpm;
[0175] Then, fluorine-modified silica sol was added dropwise into a three-necked flask at a dropping speed of 2 mL / s to 4 mL / s, and refluxed at 60°C to 80°C for 1.5 h to 2 h;
[0176] Finally, the prepared solution was filtered through a 200-mesh copper mesh to obtain a coating composition.
[0177] In some other embodiments of the present invention, an antifouling coating is provided, which is obtained by curing the coating composition of the present invention.
[0178] It can be understood that the antifouling coating of the present invention is obtained by curing the coating composition of the present invention, and thus, at least has all the beneficial effects of the coating composition. Specifically:
[0179] It can also be understood that the antifouling coating of the present invention uses a PMOS precursor with a special structure, which can be self-polymerized by a structure-directing agent to form a skeleton structure with a periodic arrangement. There are still free active points in the periodic skeleton, which may react with stains and chemicals. Through the alkoxysilane with a functionality ≥ 2 and the network skeleton formed by the ceramic precursor, free radical polymerization reaction further occurs between the free active points, so that inorganic ceramic chemical bonds are interspersed in the periodic skeleton formed by the PMOS precursor, enhancing the mechanical strength and stability of the coating structure, so that the formed coating has the characteristics of high hardness and high wear resistance, and at the same time has high scratch resistance.
[0180] The antifouling coating of the present invention has a large number of silicon-oxygen bonds, fluorine-containing groups and other groups connected to the active points of the periodic skeleton. By utilizing the periodic arrangement of the skeleton, various functional groups are orderly arranged in the skeleton, thereby reducing free active points. At the same time, the orderly arranged fluorine-containing groups in the fluorosilane can reduce the surface energy of the coating, thereby reducing the adsorption of pollutants and the corrosion of chemicals, so that the coating formed by the coating composition has excellent antifouling and anticorrosion properties.
[0181] The antifouling coating of the present invention has active points in the skeleton that physically and chemically react with the groups and ions of the coupling agent on the surface of the organic or inorganic substrate, thereby achieving a firm bond with the substrate surface and having a high bonding force.
[0182] The antifouling coating of the present invention is a transparent, wear-resistant antifouling coating. The pencil hardness of the coating can reach 9H, the number of frictions with 1kg of steel wool is greater than 4000 times, and the color difference value of the coating is ΔE≤1.5 after being stained for no less than 24 hours. The tolerable stains include: corrosive stains (including but not limited to vinegar, cola), dye stains (including but not limited to strong tea, ink), and grease stains (including but not limited to animal oil and vegetable oil). The visible light transmittance is ≥95%, and after 1000h of xenon lamp aging acceleration time, the coating does not break or turn yellow, and the color difference ΔE≤1. The chemical corrosion resistance is better than C4 level. After the coating is applied to the surface of artificial stone, the waterproofness of artificial stone is ≥95%. The bonding strength cross-cutting method level is better than level 1.
[0183] The antifouling coating of the present invention has better antifouling and anticorrosion effects than artificial stone permeable protective agents, and the effects last longer. Compared with general protective coatings, the antifouling coating has better transparency, higher hardness, and better wear resistance, and can be used on the ground for a long time.
[0184] In the antifouling coating of the present invention, the PMOS precursor can be either homemade or commercially available. Its structure conforms to the structure of the PMOS precursor defined in the present invention. Based on the structure of the PMOS precursor defined in the present invention, under the induction of a structure directing agent, a silicon-oxygen skeleton with a periodic arrangement sequence is formed by self-polymerization reaction, and the mechanical strength and stability are superior to other silicon-oxygen structures.
[0185] In the antifouling coating of the present invention, the solvent system meets environmental protection requirements, and the coating is non-toxic and tasteless after being completely cured.
[0186] In some embodiments of the present invention, the thickness of the antifouling coating is 5 μm to 15 μm.
[0187] In some other embodiments of the present invention, the present invention provides a method for preparing an antifouling coating, the method comprising:
[0188] A curing agent is added to the coating composition, mixed evenly, and then the coating is applied to the surface of the substrate, and dried to obtain the antifouling coating of the present invention.
[0189] It can be understood that the antifouling coating of the present invention is easy to construct, has undemanding curing conditions, and is suitable for large-area coating.
[0190] In some embodiments of the present invention, the method for preparing the antifouling coating may be:
[0191] After scrubbing the surface of the artificial stone substrate with alcohol and acetone respectively, leave it for at least half an hour to allow the artificial stone substrate to fully dry;
[0192] After the coupling agent and ethanol are mixed evenly, wipe them evenly on the surface of the substrate and leave them for 0.5h to 1.5h;
[0193] Add curing agent to the coating composition, stir magnetically to mix thoroughly, and then proceed with subsequent coating preparation operations. The mass ratio of the coating composition to the curing agent is between 6 and 8:1;
[0194] Spray a transparent wear-resistant and antifouling coating on the surface of the substrate, leave it alone for natural curing, and then bake it in an oven at 60°C to 80°C for 6h to 12h to form a transparent wear-resistant and antifouling coating.
[0195] In some embodiments of the present invention, the spraying is performed by air spraying with a pressure of 0.2 MPa to 0.3 MPa.
[0196] In some embodiments of the present invention, the spraying distance is 20 mm to 30 mm.
[0197] In some embodiments of the present invention, the humidity is between 40% and 60%, and the temperature is between 15°C and 30°C.
[0198] In some embodiments of the present invention, the coupling agent is at least one of KH550, KH560, A171, A151 and KHA172.
[0199] In some embodiments of the present invention, the curing agent includes at least one of 3-aminopropyltriethoxysilane and 3-glycidyloxypropyltrimethoxysilane.
[0200] In some embodiments of the present invention, the curing agent includes at least one of KH550 and KH560.
[0201] In some embodiments of the present invention, the mass ratio of the curing agent to the coating composition is 1:6-8.
[0202] In some embodiments of the present invention, by weight, when the PMOS precursor is 100 parts, the curing agent is 30 parts to 60 parts.
[0203] In some embodiments of the present invention, the substrate includes cement-based inorganic artificial stone.
[0204] In some other embodiments of the present invention, there is provided application of the antifouling coating of the present invention on the surface of cement-based inorganic artificial stone.
[0205] It can be understood that the antifouling coating of the present invention is a transparent, wear-resistant antifouling coating. When used on the surface of cement-based inorganic artificial stone, the pencil hardness of the coating can reach 9H, the number of frictions with 1kg steel wool is greater than 4000 times, and the color difference value of the coating is ΔE≤1.5 after being stained with stains for no less than 24 hours. The tolerable stains include: corrosive stains (including but not limited to vinegar, cola), dye stains (including but not limited to strong tea, ink), and grease stains (including but not limited to animal oil and vegetable oil). The visible light transmittance is ≥95%, and after 1000h of xenon lamp aging acceleration time, the coating does not break or turn yellow, and the color difference ΔE≤1. The chemical corrosion resistance is better than C4 level. After the coating is applied to the surface of artificial stone, the waterproofness of artificial stone is ≥95%. The bonding strength cross-cutting method level is better than level 1.
[0206] The antifouling coating of the present invention has better antifouling and anticorrosion effects than artificial stone permeable protective agents, and the effects last longer. Compared with general protective coatings, the antifouling coating has better transparency, higher hardness, and better wear resistance, and can be used on the ground for a long time.
[0207] In the antifouling coating of the present invention, the PMOS precursor can be either homemade or commercially available. Its structure conforms to the structure of the PMOS precursor defined in the present invention. Based on the structure of the PMOS precursor defined in the present invention, under the induction of a structure directing agent, a silicon-oxygen skeleton with a periodic arrangement sequence is formed by self-polymerization reaction, and the mechanical strength and stability are superior to other silicon-oxygen structures.
[0208] In the antifouling coating of the present invention, the solvent system meets environmental protection requirements, and the coating is non-toxic and tasteless after being completely cured.
[0209] The technical solution of the present invention will be better understood with reference to specific embodiments below.
[0210] Example 1
[0211] This embodiment first prepares a coating composition. The specific process is:
[0212] The first step is to prepare the polysiloxane solution
[0213] A1: Mix 20g ethanol and 0.1g P123 structure directing agent evenly and introduce them into a three-necked flask, keep stirring at about 1750rpm. Mix 5g catalyst (ammonia, CAS No.: 7664-41-7) and 15g deionized water evenly, and slowly drip the catalyst and deionized water mixed solution into the three-necked flask under stirring at a dripping speed of about 2.5mL / min. Adjust the solution pH to 9 and continue to reflux at 120℃ for 1.5h;
[0214] A2: The solution temperature was lowered to 80°C, 30g of ethanol and 27g of PMOS precursor (1,2-bistrimethoxysilylethane, CAS No.: 18406-41-2) were mixed and added into a three-necked flask at a dropping speed of about 2.5mL / min, and then refluxed at 80°C for 2h;
[0215] A3: Then stop heating and maintain magnetic stirring. After the three-necked flask is cooled to room temperature by air, perform silica gel column chromatography with (petroleum ether (60-90° C.) / ethyl acetate=70:1, v / v) as the mobile phase to obtain a polysiloxane solution with a periodic skeleton structure.
[0216] The second step is to prepare the modified silica sol
[0217] B1: Mix 75g ethanol, 15g ethyl orthosilicate, 14g dimethyldiethoxysilane and 24g methyltrimethoxysilane, put into a three-necked flask, and stir magnetically for 5min at a speed of about 1750rpm;
[0218] B2: After the mixture is completely stirred, slowly drip the catalyst and deionized water mixed solution into the three-necked flask under stirring at a rate of 2.5 mL / min. Adjust the pH of the solution to 9 and reflux at 80°C for 1 hour;
[0219] B3: Then, 5 g of tridecafluorooctyltriethoxysilane was added dropwise into the three-necked flask at a dropping speed of 3 mL / s; the temperature was maintained and refluxed for 2 h to obtain fluorine-modified silica sol.
[0220] Step 3: Preparation of transparent wear-resistant antifouling coating
[0221] C1: Mix 20g of ethanol and polysiloxane solution evenly, put into a three-necked flask, and keep magnetic stirring for 5 minutes. The magnetic stirring speed is 1750rpm;
[0222] C2: Then, fluorine-modified silica sol was added dropwise into a three-necked flask at a rate of 3 mL / s and refluxed at 80°C for 1.5 h;
[0223] C3: Finally, the prepared solution is filtered through a 200-mesh copper mesh to obtain a transparent wear-resistant antifouling coating. Figure 1 As shown, it can be seen that the antifouling coating according to the embodiment of the present invention has a clear and transparent appearance.
[0224] Afterwards, an antifouling coating was prepared on the surface of cement-based inorganic artificial stone. The specific process is as follows:
[0225] D1: After cleaning the surface of the artificial stone substrate with alcohol and acetone respectively, leave it for half an hour to allow the artificial stone substrate to fully dry;
[0226] D2: Mix KH550 and alcohol (1:1 volume ratio) evenly, wipe evenly on the surface of artificial stone substrate, and leave for 1 hour;
[0227] D3: Add 7g 3-aminopropyltriethoxysilane to 49g of the prepared transparent wear-resistant antifouling coating, stir magnetically for 5min to mix thoroughly, and then proceed to the subsequent coating preparation operation;
[0228] D4: Spray transparent wear-resistant and antifouling coating on the surface of artificial stone. The spraying is done by air spraying, with a pressure of 0.25MPa and a spraying distance of about 25mm. The humidity is about 50%. The temperature is about 20℃. After spraying, place it for 30 minutes to naturally cure, and then bake it in an oven at 80℃ for 12 hours to obtain a transparent wear-resistant and antifouling coating.
[0229] Example 2
[0230] This embodiment first prepares a coating composition. The specific process is:
[0231] The first step is to prepare the polysiloxane solution
[0232] A1: Mix 20g ethanol and 0.1g P123 structure directing agent evenly and introduce them into a three-necked flask, keep stirring at about 1750rpm. Mix 5g catalyst (ammonia, CAS No.: 7664-41-7) and 15g deionized water evenly, and slowly drip the catalyst and deionized water mixed solution into the three-necked flask under stirring at a dripping speed of about 2-3mL / min. Adjust the solution pH to 9-10 and continue to reflux at 120℃ for 1h;
[0233] A2: The solution temperature was lowered to 60°C, 8g of ethanol and 30g of PMOS precursor (1,1-bis(trimethoxysilylmethyl)ethylene, CAS No.: 143727-20-2) were mixed and added into a three-necked flask at a dropping speed of about 2-3mL / min, and then refluxed for 3h;
[0234] A3: Then stop heating and maintain magnetic stirring. After the three-necked flask is cooled to room temperature by air, remove the prepared solution and perform silica gel column chromatography separation using (petroleum ether (60-90°C) / ethyl acetate = 70:1, v / v) as the mobile phase to obtain a polysiloxane solution with a periodic skeleton structure.
[0235] The second step is to prepare the modified silica sol
[0236] B1: Mix 20g ethanol, 20g ethyl orthosilicate, 14g dimethyldiethoxysilane, 18g phenyltrimethoxysilane and 14g methyltrimethoxysilane, put them into a three-necked flask, and stir them magnetically for 5min at a speed of about 1750rpm;
[0237] B2: After the mixture is completely stirred, slowly drip the catalyst and deionized water mixed solution into the three-necked flask under stirring at a rate of 2.5 mL / min. Adjust the pH of the solution to 9 and reflux at 60°C for 1.5 h;
[0238] B3: Then 6 g of dodecafluoroheptylpropyltrimethoxysilane was added dropwise into the three-necked flask at a dropping rate of 3 mL / s. The temperature was maintained and refluxed for 2 h to obtain fluorine-modified silica sol.
[0239] Step 3: Preparation of transparent wear-resistant antifouling coating
[0240] C1: Mix 20g of ethanol and polysiloxane solution evenly, put into a three-necked flask, and keep magnetic stirring for 5 minutes. The magnetic stirring speed is about 1750rpm;
[0241] C2: Then, add fluorine-modified silica sol dropwise into a three-necked flask at a rate of about 3 mL / s and reflux at 60°C for 1.5 h;
[0242] C3: Finally, the prepared solution is filtered through a 200-mesh copper mesh to obtain a transparent wear-resistant antifouling coating.
[0243] Afterwards, an antifouling coating was prepared on the surface of cement-based inorganic artificial stone. The specific process is as follows:
[0244] D1: After cleaning the surface of the artificial stone substrate with alcohol and acetone respectively, leave it for half an hour to allow the artificial stone substrate to fully dry;
[0245] D2: Mix KH550 and alcohol (1:1) evenly, wipe evenly on the surface of artificial stone substrate, and leave for 1 hour;
[0246] D3: Add 7g 3-aminopropyltriethoxysilane to 49g of the prepared transparent wear-resistant antifouling coating, stir magnetically for 5min to mix thoroughly, and then proceed to the subsequent coating preparation operation;
[0247] D4: Spray transparent wear-resistant and antifouling coating on the surface of artificial stone. The spraying is done by air spraying, with a pressure of 0.25MPa and a spraying distance of about 25mm. The humidity is about 50%. The temperature is about 20℃. After spraying, place it for 30 minutes to naturally cure, and then bake it in an oven at 80℃ for 12 hours to obtain a transparent wear-resistant and antifouling coating.
[0248] Comparative Example 1
[0249] The main difference between this comparative example and Example 1 is that no poly-PMOS precursor solution is added.
[0250] The specific preparation process is:
[0251] (1) 60 g of ethanol, 15 g of ethyl orthosilicate, 14 g of dimethyldiethoxysilane and 24 g of methyltrimethoxysilane were mixed evenly, placed in a three-necked flask, and magnetically stirred for 5 min at a magnetic stirring speed of 1750 rpm;
[0252] (2) After the mixture is completely stirred, slowly drip 5 g of catalyst (ammonia, CAS No.: 7664-41-7) and 15 g of deionized water into the three-necked flask under stirring at a rate of 2.5 mL / min. Adjust the pH of the solution to 9 and reflux at 80°C for 1 h.
[0253] (3) Then, 5 g of tridecafluorooctyl triethoxysilane was added dropwise into the three-necked flask at a rate of 2-4 mL / s. The temperature was maintained and refluxed for 2 h to obtain fluorine-modified silica sol;
[0254] (4) finally filtering the prepared solution through a 200-mesh copper mesh to obtain a transparent wear-resistant antifouling coating;
[0255] (5) After cleaning the surface of the artificial stone substrate with alcohol and acetone respectively, leave it for half an hour to allow the artificial stone substrate to fully dry;
[0256] (6) Mix KH550 and alcohol (1:1) evenly, wipe evenly on the surface of the artificial stone substrate, and leave it for 1 hour;
[0257] (7) 7 g of 3-aminopropyltriethoxysilane was added to 49 g of the prepared transparent wear-resistant antifouling coating, and the mixture was stirred magnetically for 5 min to be thoroughly mixed to obtain a coating composition.
[0258] Afterwards, an antifouling coating was prepared on the surface of cement-based inorganic artificial stone. The specific process is as follows:
[0259] Spray transparent wear-resistant and antifouling paint on the surface of artificial stone, using air spraying, pressure 0.25MPa, spraying distance about 25mm. Humidity is about 50%. Temperature is about 20℃. After spraying, place it for 30 minutes to naturally cure, and then bake it in an oven at 80℃ for 12 hours to obtain the coating.
[0260] Comparative Example 2
[0261] The main difference between this comparative example and Example 2 is that no fluorine-modified silica sol is added.
[0262] The specific preparation process is:
[0263] (1) Mix 60 g of ethanol and 0.1 g of P123 structure-directing agent evenly and introduce them into a three-necked flask while stirring.
[0264] The speed is around 1750rpm;
[0265] (2) Mix 5g of catalyst (ammonia, CAS No.: 7664-41-7) and 15g of deionized water. Slowly drip the catalyst and deionized water mixed solution into a three-necked flask under stirring at a rate of 2.5mL / min. Adjust the pH of the solution to 9 and continue to reflux at 120℃ for 1h;
[0266] (3) The solution temperature was lowered to 60°C, and 6 g of ethanol and 34 g of PMOS precursor (bis(3-trimethoxysilylpropyl)methyl methacrylate, CAS No.: 82985-35-1) were mixed and added into a three-necked flask at a dropping rate of about 2.5 mL / min.
[0267] Then reflux for 3h;
[0268] (4) Then, the heating is stopped, and the magnetic stirring is maintained. After the three-necked flask is cooled to room temperature by air, the prepared solution is removed, and silica gel column chromatography is performed using (petroleum ether (60-90° C.) / ethyl acetate = 70:1, v / v) as a mobile phase to obtain a polysiloxane solution having a periodic skeleton structure;
[0269] (5) finally filtering the prepared solution through a 200-mesh copper mesh to obtain a transparent wear-resistant antifouling coating;
[0270] (6) After cleaning the surface of the artificial stone substrate with alcohol and acetone respectively, leave it for half an hour to allow the artificial stone substrate to fully dry;
[0271] (7) Mix KH550 and alcohol (1:1) evenly, wipe evenly on the surface of the artificial stone substrate, and leave it for 1 hour.
[0272] (8) 7 g of 3-aminopropyltriethoxysilane was added to 49 g of the prepared transparent wear-resistant antifouling coating, and the mixture was stirred magnetically for 5 min to be thoroughly mixed to obtain a coating composition.
[0273] Afterwards, an antifouling coating was prepared on the surface of cement-based inorganic artificial stone. The specific process is as follows:
[0274] The transparent wear-resistant and antifouling coating is sprayed on the surface of the artificial stone by air spraying, with a pressure of about 0.25 MPa and a spraying distance of about 25 mm. The humidity is about 50%. The temperature is 20°C. After spraying, it is placed for 30 minutes for natural curing, and then placed in an oven at 80°C for 12 hours to obtain the transparent wear-resistant and antifouling coating of the invention.
[0275] Comparative Example 3
[0276] This comparative example first prepared a coating composition. The specific process is:
[0277] The first step is to prepare the polysiloxane solution
[0278] A1: Mix 20g of ethanol and 58g of PMOS precursor (N-[vinyl-bis(3-trimethoxysilylpropylamino)silyl]-3-trimethoxysilylpropane-1-amine, CAS No.: 112667-69-3) evenly and introduce them into a three-necked flask, keep stirring at a speed of about 1750rpm. Mix 5g of catalyst (ammonia, CAS No.: 7664-41-7) and 15g of deionized water evenly, and slowly drip the catalyst and deionized water mixed solution into the three-necked flask under stirring, with a dripping speed of about 2.5mL / min, adjust the solution pH to 11, and continue to reflux at 80℃ for 1.5h;
[0279] A2: Mix 6g ethanol and 0.1g P123 structure directing agent, add into a three-necked flask at a drop rate of about 6mL / min, then cool to 40℃ and reflux for 4h;
[0280] A3: Then stop heating and maintain magnetic stirring. After the three-necked flask is cooled to room temperature by air, remove the prepared solution and perform silica gel column chromatography separation using (petroleum ether (60-90°C) / ethyl acetate = 70:1, v / v) as the mobile phase to obtain a polysiloxane solution with a periodic skeleton structure.
[0281] The second step is to prepare the modified silica sol
[0282] B1: Mix 20g ethanol, 15g ethyl orthosilicate, 14g dimethyldiethoxysilane and 24g methyltrimethoxysilane, put into a three-necked flask, and stir magnetically for 5min at a speed of about 1250rpm;
[0283] B2: After stirring thoroughly, slowly drip the catalyst and deionized water mixed solution into the three-necked flask under stirring at a rate of 6 mL / min. Adjust the solution pH to 9 and reflux at 40°C for 3 h.
[0284] B3: Then 5 g of tridecafluorooctyltriethoxysilane was added dropwise into the three-necked flask at a dropping rate of 3 mL / s. The temperature was maintained and refluxed for 1 h to obtain fluorine-modified silica sol.
[0285] Step 3: Preparation of transparent wear-resistant antifouling coating
[0286] C1: Mix 20g of ethanol and fluorine-modified silica sol evenly, put them into a three-necked flask, and keep magnetic stirring for 5 minutes. The magnetic stirring speed is 1750rpm;
[0287] C2: Then, polysiloxane solution was added dropwise into the three-necked flask at a rate of 3 mL / s and refluxed at 100°C for 0.5 h;
[0288] C3: Finally, the prepared solution is filtered through a 200-mesh copper mesh to obtain a transparent wear-resistant antifouling coating.
[0289] Afterwards, an antifouling coating was prepared on the surface of cement-based inorganic artificial stone. The specific process is as follows:
[0290] D1: After scrubbing the surface of the artificial stone substrate with alcohol and acetone respectively, leave it for half an hour to allow the artificial stone substrate to fully dry.
[0291] D2: Mix KH550 and alcohol (1:1) evenly, wipe evenly on the surface of artificial stone substrate, and leave for 1 hour.
[0292] D3: Add 7g 3-aminopropyltriethoxysilane to 49g of the prepared transparent wear-resistant and antifouling coating, stir magnetically for 5min to mix thoroughly, and then proceed with the subsequent coating preparation operation.
[0293] D4: Spray transparent wear-resistant and antifouling coating on the surface of artificial stone, using air spray, pressure 0.25MPa, spray distance about 25mm, humidity 50%, temperature 20℃. After spraying, place it for 30 minutes to cure naturally, then bake it in an oven at 80℃ for 12 hours to obtain a transparent wear-resistant and antifouling coating.
[0294] Test Case
[0295] The pencil hardness, adhesion, abrasion resistance, stain resistance, chemical resistance, waterproof performance, weather resistance and transmittance of the coatings prepared in the examples and comparative examples were tested.
[0296] The pencil hardness test is based on the standard GB / T 6739-2006 "Paints and varnishes - Determination of film hardness by pencil method".
[0297] The adhesion test is based on the standard GB / T 9286-2021 "Scratch test for paint and varnish films".
[0298] The wear resistance test is based on the scratch resistance test method in GB / T 22374-2018 Floor Decoration Materials. Under a load of 1 kg, 0000# steel wool is used to rub the coating surface back and forth, with a friction frequency of 1 Hz and a friction length of about 50 mm. The number of frictions is 4000 times, and the appearance of the coating after wear is observed.
[0299] The stain resistance test is based on the stain resistance test part of JC / T 908-2013 "Artificial Stone". The color difference between the contaminated area and the uncontaminated area is measured by a colorimeter as the test result.
[0300] The chemical resistance test is based on the standard GBT35157-2017 "Resin-type synthetic stone slabs".
[0301] The waterproof performance test is based on Appendix A of JC / T 973-2005 "Industry Standard for Natural Stone Protective Agents for Architectural Decoration".
[0302] The weather resistance test is based on the standard GB / T 1865-2009 "Artificial weathering and artificial radiation exposure of paints and varnishes to filtered xenon arc radiation".
[0303] The transmittance test is based on the visible light band in GB 5433-2008 "Determination of transmittance of daily glass".
[0304] The test results are shown in Table 1.
[0305] Table 1 Coating performance test results
[0306] Test items Example 1 Example 2 Comparative Example 1 Comparative Example 2 Comparative Example 3 Pencil hardness 9H 9H 5H 4H 6H Adhesion Level 0 Level 0 Better than level 1 Better than level 1 Better than level 1 Wear resistance Not ground through Not ground through Expose the substrate Expose the substrate Expose the substrate Stain resistance ΔE≤1.5 ΔE≤1.5 ΔE≤4 ΔE≤7 ΔE≤6 Chemical resistance Better than C4 Better than C4 Better than C2 Better than C3 Better than C2 Waterproof ≥95% ≥95% ≥80% ≥90% ≥85% Weather resistance ΔE≤1 ΔE≤1 ΔE≤3 ΔE≤3 ΔE≤3 Transmittance 95% 95% 95% 95% 95% Film thickness 8.5μm 7.9μm 11.2μm 9.2μm 8.4μm
[0307] It can be seen from the test results in Table 1 that the antifouling coating formed by the coating composition of the present invention after drying is a transparent and wear-resistant antifouling coating.
[0308] The pencil hardness of the coating can reach 9H.
[0309] The number of frictions of 1kg steel wool is greater than 4000 times. The wear resistance test results of the coatings of the embodiment and the comparative example are as follows: Figure 2 shown.
[0310] The stain resistance test results of the coatings of the embodiment and the comparative example are as follows: Figure 3 shown.
[0311] The color difference of the coating is ΔE≤1.5.
[0312] Tolerable stains include: corrosive stains (including but not limited to vinegar, cola), dye stains (including but not limited to strong tea, ink), and grease stains (including but not limited to animal oil and vegetable oil).
[0313] Visible light transmittance ≥95%.
[0314] After 1000h of xenon lamp accelerated aging time, the coating does not break or turn yellow, and the color difference ΔE≤1.
[0315] Chemical corrosion resistance is better than C4 grade.
[0316] After the coating is applied on the surface of artificial stone, the waterproofness of the artificial stone is ≥95%.
[0317] The bonding strength can reach level 0 by the cross-cutting method.
[0318] In Comparative Example 3, due to the differences in the order, speed, and proportion of raw material addition, it is easy to cause the PMOS precursor to be partially uncrosslinked or incompletely crosslinked to form a three-dimensional network skeleton structure during the preparation process, resulting in a decrease in the hardness of the coating. At the same time, there are more free active points in the structure, so the chemical resistance, weather resistance and other properties are reduced. Incompletely cross-linked active points will also compete for the fluorine-modified solution, which will lead to a decrease in the content of effective substances in the coating. There are more other substances or active substances, so the coating performance is reduced. At the same time, if it is not separated, there are more residual active substances in the polysiloxane solution, which compete for the active groups added to the fluorine-modified solution, resulting in less effective substance components in the overall coating and an increase in other low-performance substances, so its coating performance is reduced.
[0319] The present invention has been described in detail above in conjunction with the embodiments, but the present invention is not limited to the above embodiments, and various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A coating composition, characterized in that The preparation raw materials include a PMOS precursor, a structure directing agent, a ceramic precursor, an alkoxysilane and a fluorosilane, wherein the functionality of the alkoxysilane is ≥2, and the PMOS precursor has a structure as shown in formula (I) or formula (II): Wherein, R1 and R2 are independently selected from at least one of alkanes, alkenes, and amines, and R3 is selected from methyl or ethyl; The coating composition is prepared by the following method: Using the structure directing agent, PMOS precursor, organic solvent, catalyst and water, a polysiloxane solution is prepared; Using the ceramic precursor, alkoxysilane, fluorosilane, organic solvent, catalyst and water, a fluorine-modified silica sol is prepared; After mixing the polysiloxane solution and the organic solvent, adding the fluorine-modified silica sol, and refluxing to obtain the coating composition; The preparation method of the polysiloxane solution is: A1: Mix the structure directing agent and the organic solvent, mix the catalyst and water, add the mixed solution of the catalyst and water to the mixed solution of the structure directing agent and the solvent under stirring, adjust the pH, and reflux at 100° C. to 120° C. for 1 h to 1.5 h; A2: Cooling the solution prepared in step A1 to 60°C-80°C, mixing the organic solvent and the PMOS precursor, adding the mixture to the cooled solution prepared in step A1, and reflux for 2h-3h; A3: Stop heating, cool to room temperature under stirring, and perform silica gel column chromatography to obtain the polysiloxane solution; The structure directing agent comprises at least one of a triblock copolymer, hexadecyltrimethylammonium bromide, hexadecylpyridinium bromide salt, and alkyltrimethylammonium chloride; The ceramic precursor includes at least one of zirconium n-propoxide, tetraethyl orthosilicate and butyl orthotitanate.
2. The coating composition according to claim 1, characterized in that In parts by weight, the raw materials for preparation include: PMOS precursor: 100 parts, Structure directing agent: 0.1~0.5 parts, Ceramic precursor: 50~90 parts, Alkoxysilane: 50 to 200 parts, Fluorosilane: 10 to 20 parts.
3. The coating composition according to claim 1, characterized in that The alkoxysilane includes at least two of methyltriethoxysilane, methyltrimethoxysilane, dimethyldimethoxysilane, 3-[(2,3)-epoxypropyloxy]propylmethyldimethoxysilane, phenyltriethoxysilane, phenyltrimethoxysilane and dimethyldiethoxysilane.
4. The coating composition according to claim 1, characterized in that The fluorosilane includes at least one of dodecafluoroheptylpropyltrimethoxysilane, perfluorooctyltrimethoxysilane, tridecafluorooctyltriethoxysilane and heptadecafluorodecyltrimethoxysilane.
5. The coating composition according to any one of claims 1 to 4, characterized in that In parts by weight, when the PMOS precursor is 100 parts, the preparation raw materials also include: Organic solvent: 300~500 parts, Catalyst: 10~15 parts, Water: 30~50 parts.
6. The coating composition according to claim 5, characterized in that The organic solvent includes at least one selected from methanol, ethanol, n-propanol and n-butanol.
7. The coating composition according to claim 5, characterized in that The catalyst includes at least one of an inorganic base, an alkali metal hydroxide or a metal carboxylate.
8. The coating composition according to claim 1, characterized in that The preparation method of the fluorine-modified silica sol is: B1: mixing the ceramic precursor, alkoxysilane and organic solvent; B2: Mix the catalyst and water, add the mixed solution of the catalyst and water to the mixed solution prepared in step B1 under stirring, adjust the pH, and reflux at 60°C to 80°C for 1h to 1.5h; B3: adding the fluorosilane to the mixed solution prepared in step B2, and continuing to reflux for 1 h to 1.5 h to obtain the fluorine-modified silica sol.
9. An antifouling coating, characterized in that: Obtained by curing the coating composition according to any one of claims 1 to 8.
10. Use of the antifouling coating as claimed in claim 9 on the surface of cement-based inorganic artificial stone.
Citation Information
Patent Citations
Aqueous silane systems based on bis(trialkoxysilylalkyl)amines
CN101376710A
Coating agent, maintenance-free stone tile coated by the same, and method for producing the tile
CN106147595A